Role of stress-related hormones in plant defence during early infection of the cyst nematode Heterodera schachtii in Arabidopsis - Kammerhofer, Nina (The New phytologist, 2015)
© 2015 The Authors. New Phytologist © 2015 New Phytologist Trust.